Contrasts in Religion, Community, and Structure at Three Homeless Shelters: Changing Lives - Jindra, Ines W. (Routledge Studies in Religion Ser., 2021)
Intro -- Endorsements -- Half Title -- Series Page -- Title Page -- Copyright Page -- Dedication -- Contents -- Tables -- Acknowledgments -- 1. Introduction: Homelessness and faith-based organizations -- Three contrasting homeless shelters -- The extent and picture of homelessness in the United States -- Explanations of homelessness -- Nonprofits that address homelessness -- Explanations/theories of pathways out of homelessness -- Individual factors, community, and social support -- The role of religion, spirituality, and faith-based organizations -- The role of religion and spirituality in overcoming social problems -- Faith-based versus secular organizations -- The spectrum of faith-based organizations -- Criticisms of faith-based organizations -- Goals and plan of the book -- Notes -- References -- 2. Theoretical concepts and methods -- Religion, lived religion, and spirituality -- Religious conversion -- The toolkit approach and further developments -- Theory and method: The narrative interview, participants, and the concept of the (problematic) biographical trajectory -- Notes -- References -- 3. Religion and spirituality, community, and program structure at Grace Ministries, a faith-permeated organization -- Introducing Grace Ministries -- Biography, religion and spirituality, community, and structure at Grace Ministries -- Several case studies -- Case study 1: Julia's narrative: A story of personal transformation, self-reflexivity, and growth -- Taking a deeper look: Reliance on God and willingness to change -- Case study 2: Tom's narrative: A story of religious transformation and personal growth -- Taking a deeper look: The central role of forgiveness -- Case study 3: Derrick's narrative: Strong use of religious tools and personal insights -- Taking a deeper look: Taking a good look at the reasons for homelessness.